Intraoperative ketorolac for pediatric tonsillectomy: Effect on post-tonsillectomy hemorrhage and perioperative analgesia. (November 2020) - Rabbani, Cyrus C.; Pflum, Zachary E.; Ye, Michael J.; Gettelfinger, John D.; Sadhasivam, Senthil; Matt, Bruce H.; Dahl, John P.
Abstract: Objective: Determine the impact of ketorolac on post-tonsillectomy hemorrhage (PTH) and narcotic administration in children undergoing tonsillectomy. Methods: Retrospective case series from 2013 to 2017. Patients younger than 18 years undergoing tonsillectomy were included. PTH was the primary outcome measured. Secondary measures include percentage of patients requiring surgical intervention for PTH, average time to PTH, the number of post-operative opioid doses, and average post-operative opioid dose. Statistical methods include Chi-square, Wilcoxon rank sum, and binary logistic regression analyses. Results: During the study period, 669 patients received a single intraoperative dose of ketorolac (K+) and 653 patients did not receive ketorolac (K-). No differences were found in the rate of PTH (K- 6.5% vs. K+ 5.3%, RR = 0.82, 95% CI = 0.53 to 1.29, p = 0.40), surgical control of PTH (K- 4.0% vs. K+ 3.5%, RR = 0.87, CI = 0.51 to 1.51, p = 0.62), or average time [SD] to PTH (K- 6.0 [4.2] vs. K+ 5.2 [4.9] days; difference = 0.8 days; 95% CI, −1.3 to 2.9; p = 0.45). K+ patients had fewer post-operative opioid doses [SD] (K- 1.86 [1.14] vs. K+ 1.59 [1.23]; difference = −0.27; 95% CI, −0.053 to −0.49, Cohen d = 0.23) and a lower average opioid dose [SD] (K- 0.041 [0.032] vs. K+ 0.035 [0.030] mg/kg; difference = −0.006 mg/kg; 95% CI, −0.0003 to −0.012; Cohen d = 0.19). Conclusion: Ketorolac did not increase risk of hemorrhage following tonsillectomy and decreased narcotic use.